The Relationship of Knowledge with Community Behavior in First Aid for Traffic Accidents in Tenilo Village, Limboto District, Gorontalo Regency - Haslinda Damansyah; Susanty Monoarfa; Sity Nurlela Pasi (PROMOTOR, 2024)
First aid is the first treatment for accident victims before being handled by medical personnel to prevent victims from more severe injuries. Community behavior and community knowledge play an important role in the success of first aid. This study aims to determine the relationship of knowledge with community behavior in first aid for traffic accidents in the Tenilo sub-district. Quantitative research method with descriptive and cross-sectional design. A sample of 68 respondents was taken by accidental sampling technique. Data were obtained by observation and Chi-Square analysis  (a = 0.05). The results showed good public knowledge 40 (58.8%), poor knowledge 12 (17.6%) and good community behavior 13 (19.1%), and less good 3 (4.4%). The results of the study from the analysis test p = 0.000 so that it was concluded that there was a relationship between knowledge and community behavior in first aid traffic speed in Tenilo Village.